1999
DOI: 10.1200/jco.1999.17.12.3767
|View full text |Cite
|
Sign up to set email alerts
|

Patients With t(8;21)(q22;q22) and Acute Myeloid Leukemia Have Superior Failure-Free and Overall Survival When Repetitive Cycles of High-Dose Cytarabine Are Administered

Abstract: These data demonstrate that failure-free survival and overall survival of patients with t(8;21)(q22;q22) may be compromised by treatment approaches that do not include sequential high-dose cytarabine therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
130
5
9

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(154 citation statements)
references
References 20 publications
10
130
5
9
Order By: Relevance
“…This finding appears to be specifically due to the favorable outcome of t(8;21) patients when treated with the intensive induction/consolidation regimen, whereas the DFS of inv(16) patients seemed to be unaffected by the kind of therapy employed. A favorable outcome, in t(8;21) cases, could thus be related not only with the number of repeated cycles of high-dose AraC as previously reported, 40 but with alternative intensive chemotherapy schedules as well. In the 'intermediate' subgroup, intensive induction did not appear to improve DFS with respect to standard induction.…”
Section: Leukemiasupporting
confidence: 50%
“…This finding appears to be specifically due to the favorable outcome of t(8;21) patients when treated with the intensive induction/consolidation regimen, whereas the DFS of inv(16) patients seemed to be unaffected by the kind of therapy employed. A favorable outcome, in t(8;21) cases, could thus be related not only with the number of repeated cycles of high-dose AraC as previously reported, 40 but with alternative intensive chemotherapy schedules as well. In the 'intermediate' subgroup, intensive induction did not appear to improve DFS with respect to standard induction.…”
Section: Leukemiasupporting
confidence: 50%
“…4 However, relapses still occur in about 30% of the cases. Initial features such as a high initial white blood cell count (WBC), WBC index, CD56 expression, del (9q) in addition to t(8;21) or extramedullary disease have been associated with an increased risk of relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Historically, CBF AML was treated with standard cytarabine plus anthracycline induction chemotherapy followed by one or several consolidation courses of high-dose cytarabine. Studies comparing consolidation strategies reported cure rates in CBF AML of 30-40% with one highdose cytarabine consolidation versus 50-70% with 3-4 consolidation courses [67,68]. Recent studies have used induction and consolidation courses of high-dose cytarabine in combination with fludarabine and idarubicin, as well as the addition of GO 3 mg/m 2 3 1 during induction and one consolidation course.…”
Section: Core Binding Factor Amlmentioning
confidence: 99%